2000
DOI: 10.1111/j.1528-1157.2000.tb00123.x
|View full text |Cite
|
Sign up to set email alerts
|

Do Reactive Post‐Resection “Injury” Spikes Exist?

Abstract: Summary:Purpose: New post-resection spikes on electrocorticography (ECoG) after lesionectomy in patients with seizures may represent residual epileptogenic tissue or presumed reactive injury spikes. We investigated the existence of postresection injury spikes by eliminating the possibility of residual epileptogenic tissue.Methods: Preresection and post-resection ECoG was performed on seven patients with an intra-axial neocortical tumor (glioblastoma multiforme or metastasis) and no history of seizures. All tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
17
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 39 publications
3
17
0
Order By: Relevance
“…We believed that this observation was most in keeping with “activation by partial excision,” as first described by Penfield and Jasper (5), related to a decreased threshold for the expression of epileptiform activity in acutely disconnected epileptogenic cortex (4). As no preresection chemical activation was carried out at ECoG in the study of Schwartz et al (1), the existence of new postresection spikes cannot with certainty be taken as evidence of their induction by surgical injury during lesionectomy. Nevertheless, there is evidence that transient epileptic foci can be induced by nonresective surgical manipulation of the neocortex, albeit with a different high firing rate, compared to the low firing rate of postresection spikes (6), and so questions remain.…”
supporting
confidence: 56%
See 2 more Smart Citations
“…We believed that this observation was most in keeping with “activation by partial excision,” as first described by Penfield and Jasper (5), related to a decreased threshold for the expression of epileptiform activity in acutely disconnected epileptogenic cortex (4). As no preresection chemical activation was carried out at ECoG in the study of Schwartz et al (1), the existence of new postresection spikes cannot with certainty be taken as evidence of their induction by surgical injury during lesionectomy. Nevertheless, there is evidence that transient epileptic foci can be induced by nonresective surgical manipulation of the neocortex, albeit with a different high firing rate, compared to the low firing rate of postresection spikes (6), and so questions remain.…”
supporting
confidence: 56%
“…Nevertheless, there is evidence that transient epileptic foci can be induced by nonresective surgical manipulation of the neocortex, albeit with a different high firing rate, compared to the low firing rate of postresection spikes (6), and so questions remain. As suggested by Schwartz et al (1), larger follow‐up studies using their design, preferably including preresection chemical activation, may hopefully provide more definitive conclusions.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…[3][4][5][6][7] Especially ictiform spike patterns, consisting of recruiting, repetitive bursting, and continuous rhythmic spiking patterns, are considered markers of epileptic brain tissue, and it is advocated that those areas should be removed to achieve seizure freedom. 16 Discriminating between epileptic red and meaningless green spikes is difficult. [12][13][14][15] Residual spikes in post-ECoG may arise from surgical manipulation of the neocortex at the resection margin.…”
mentioning
confidence: 99%
“…It is well-known that epileptiform discharges are not pathognomonique for epilepsy and could be observed in subjects without any seizures (Sam and So 2001). Moreover, it has been shown that interictal « injury » spikes eventually recorded in the postoperative period are not associated with an increased risk of seizures (Schwartz, Bazil et al 2000),a result further confirmed in patients with meningioma undergoing surgery (Rothoerl, Bernreuther et al 2003).…”
Section: -6 What Is the Role Of Eeg In Clinical Management Of Bte ?mentioning
confidence: 92%